Temporal distribution of Benthic Macroinvertebrate Communities from Tropical Forest Stream in Gunung Pulai Recreational Forest, Johor, Peninsular Malaysia - Nor Zaiha, A.; Mohd Ismid, M.S.; Salmiati, (Universiti Kebangsaan Malaysia, 2015)
Temporal changes of Ephemeroptera, Plecoptera and Trichoptera (EPT) communities were investigated at the study area of Gunung Pulai Recreational Forest, Johor, Malaysia. Taxa diversity were also studied to determine the seasonality impact on certain benthic communities. Sampling of aquatic insects were carried out from November 2012 to July 2013 using rectangular dip net. As a result, more EPT were found during the dry season (1533 individuals) compared to wet season (321 individuals). Concomitantly, higher diversity was also recorded in the dry season. Among these three investigated orders, Trichoptera represented the most diverse community with three families recorded, followed by Plecoptera (2 families) and Ephemeroptera (1 family). Caddisfly family Hydropsychidae were found to be abundant in the study area. Therefore, seasonality impact on EPT assemblage at Gunung Pulai Recreational Forest is extremely evident.